Influence of Cu doping on physical and photo-electrochemical properties of CdS thin films prepared by RF magnetron sputtering. (October 2021) - Wang, Shilin; Zhang, Xiang; Bie, Jiaying; Gong, HuiPei; Cao, Meng; Zhang, Shan; Jiang, Yucheng; Shen, Yue; Wang, Linjun
Abstract: In this paper, Cu doped CdS thin films were prepared on FTO substrates by RF magnetron sputtering and then were annealed at 350 °C–425 °C in vacuum for 20 min. The influences of different Cu-doped concentrations (Cu 4.1, 5.4, 7.3, 9.1 at%) on morphological, structural, optical properties and photo-electrochemical (PEC) properties of CdS thin films were investigated. The PEC characterizations indicated that the photocurrent densities of CdS:Cu (Cu 4.1, 5.4, 7.3, 9.1 at%) thin films increased from 0.94, 1.28, 1.86, 1.91 mA cm −2 to 1.33, 1.89, 2.40, 3.16 mA cm −2 after annealing. And the PEC properties of CdS:Cu thin films annealed at different temperatures were also studied. FTO/annealed CdS:Cu/Pt photoanode were fabricated to enhance the photocurrent activity and the photocurrent density of FTO/annealed CdS:Cu/5 nm Pt is 1.5 times larger than that of the CdS:Cu electrode without Pt cocatalyst. Highlights: CdS:Cu thin films were firstly prepared by magnetron sputtering method. PEC properties of n type CdS:Cu thin films were firstly studied. FTO/CdS:Cu/Pt improved PEC performances of CdS:Cu thin films.